IMPACT OF ONLINE CUSTOMER REVIEWS AND RATINGS ON ELECTRONIC PRODUCT PURCHASES: A TOKOPEDIA PLATFORM SURVEY AMONG PRODUCTIVE AGE CONSUMERS IN JAMBI CITY - Ikhsan, Feyza Muhammad; Yacob, Syahmardi; Suleman, Dede; Sabrina, Hanan Laras (Journal of Business Studies and Management Review, 2023)
This research aims to elucidate the impact of Online Customer Reviews and Online Customer Ratings on the decision-making process for online purchases on the E-Commerce platform Tokopedia. The study focuses on residents of Jambi City who are of productive age. A purposive sampling method was employed to select 100 respondents as the sample size for this study. Data collection was conducted through a survey questionnaire, and this primary data was analysed using multiple linear regression techniques, utilising the SPSS software for Windows. The findings of this analysis reveal that Online Customer Reviews positively influence purchasing decisions. In contrast, Online Customer Ratings were found to have no significant effect on these decisions. This suggests that while the content of customer reviews plays a crucial role in shaping consumer behaviour and choices on the Tokopedia platform, the numerical ratings assigned by customers do not significantly sway purchasing decisions. These results offer valuable insights into consumer behaviour in the digital marketplace, particularly in the context of e-commerce platforms like Tokopedia, and can inform strategies for online retailers and marketers in optimising customer engagement and sales conversion.